BIOLOGICAL CHARACTERISTICS OF STAPHYLOCOCCUS AUREUS ISOLATES RECOVERED FROM MILK AND DAIRY PRODUCTS MANUFACTURED IN THE REPUBLIC OF CRIMEA - I. V. Borodkina (Ветеринария сегодня)
Staphylococci are one of the causes of food poisoning in many countries of the world. Intoxication occurs due to staphylococcal exotoxins entering the human body. One of the main sources of staphylococcal toxins is milk and dairy products contaminated with pathogenic staphylococci. Staphylococcus aureus has the greatest sanitary and hygienic importance. In 2016–2018 168 samples of ready-to-eat dairy products were tested for Staphylococcus aureus in the Food Safety Laboratory of the FGBI “ARRIAH” in the Republic of Crimea. The tests were performed according to GOST 30347-2016 “Milk and dairy products. Methods of Staphylococcus aureus detection”. Biochemical properties of the recovered isolates were studied using Vitek 2 Compact analyzer. It was established that the following groups of products are contaminated with Staphylococcus aureus to the greatest extent: butter (20%), sour cream (9.09%), curd and curd products (4.55%), pasteurized milk in the consumer packaging (4.35%). The basic biological characteristics of the isolates have been studied and their antimicrobial resistance has been determined. All the isolated Staphylococcus aureus cultures demonstrated a 100% sensitivity to benzylpenicillin, oxacillin, imipenem, ticarcillin, meropenem, ciprofl oxacin, ofl oxacin, gentamicin, amikacin, doxycycline, tetracycline, rifampin, chloramphenicol, cefotaxime, ceftriaxone, trimethoprim and were 100% resistant to enrofl oxacin. Resistance to streptomycin was determined in 28.6% of isolates, and 14.3% of isolates were resistant to vancomycin. Methicillin-resistant staphylococci were not detected among the bacteria.